Studies of neutrophil production and turnover in grey collie dogs with cyclic neutropenia - Dale, D. C. (1972)
12 grey collie dogs had cyclic neutropenia with the neutropenia recurring at 11.8±0.1-day intervals. The recovery from neutropenia was accompanied by a single wave of myeloid proliferation, an increase in marrow myeloid-labeling indices, and an increase in serum muramidase levels. After recovery from neutropenia during the period when blood neutrophils (PMN) were normal or increased, marrow myeloid precursors became scarce. The decline in marrow precursors and marrow PMN reserves heralded the recurrence of neutropenia. Neither diisopropyl fluorophosphate (DF(32)P) leukokinetic studies nor the rate of development of neutropenia suggested shortened PMN survival as a mechanism for the neutropenia. These studies indicate that the cyclic neutropenia is due to a regularly recurring failure in PMN production.